Definition of rational modes of operation of baking ovens - Ковальов, Олександр Володимирович (Technology audit and production reserves, 2014)
The flue gas temperature is one of the main variables that are most sensitive to changes in load in industrial ovens. This temperature in turn is associated with the loss of heat from the flue gases. The last value determines the change in fuel consumption, not directly related to the load. Therefore, the problem of determining a rational oven load is reduced mainly to establish the exact or approximate relation tf1=f(G). The authors is studied the work at alternating mode of ovens with recirculation of combustion products - the most common type of baking ovens. In these furnaces load increase leads to an increase of tf1, and decrease - to decrease of tf1. Increasing the temperature of the flue gas with increasing of oven productivity is explained by the fact that productivity causes a corresponding change in the heat flow to the working chamber of the oven. This change is due to increased fuel consumption and increasing the initial temperature of the heating gases. The growth in the total enthalpy heat transfer ΔQ gas determines the increase of them, which leads to increase of tf1. Thus, the change in heat flow into the working chamber is caused by a change in the temperature difference of the heating gases. The calculations show that the change in different modes of temperature difference, calculated as the difference between the average temperature of the heating gas and the walls of the working chamber by the law of convective heat transfer, well reflects the change under the same conditions. The obtained research can be applied to bakeries, at installation and after repair of baking ovens in order to obtain high-quality products with minimal cost of fuel-energy resources.